Estudio de iones presentes en el agua potable, en sectores con suministro limitado de la provincia de trujillo, por el método de cromatografía ionica - Alva Díaz, Pierina Susana (2018)
At the beginning of the year 2017, Peru was hit by heavy rains, as a result of these floods were generated, overflowing streams and alluviums throughout the country; all these events are cataloged as " Fenómeno del niño costero”. The Province of Trujillo was not alien to this phenomenon that has caused contamination mainly of the waters, the levels of contamination of the waters also caused the paralyzation of the Potabilization Plant administered by SEDALIB, with this the quality of potable water that is supplied to the Province of Trujillo in relation to ions, could exceed the Maximum Permissible Limits and cause serious problems in the Health of the Population. Through the ion chromatography method, the present project seeks to identify and quantify the presence of fluoride ions (F-), bromide (Br-), chloride (Cl-), nitrate (NO3-), nitrite (NO2-) ), sulfate (SO42-) and phosphate (PO43-), present in the drinking water supplied to the Sectors whose supply is limited, taking as reference for the study the following 10 Sectors of the Province of Trujillo: Florencia de Mora, Porvenir-Rio Seco, Poroto, El Milagro, Menocucho, Laredo, Huanchaco, La Esperanza, Simbal and Salaverry. The results obtained indicate that the drinking water supplied to the 10 sectors mentioned above has ions of: fluoride (F-), bromide (Br-), chloride (Cl-), sulfate (SO42-) within the LMP, regarding the phosphate ion (PO43-) in some sectors it has been possible to find levels above 1000mg / L of concentration. Contamination by nutrients whose compounds are phosphates can alter hemoglobin and prevent the transport of oxygen to tissues